“In data they trust”: the poetics of citizen-generated data in Brazilian cannabis activism - Alves, Guilherme Queiroz (AoIR Selected Papers of Internet Research, 2026)
What happens when grassroots organizations decide to produce data? What forms of legitimization must their situated knowledge undergo to be recognized as actionable evidence? And who ultimately decides what counts (and what does not count) as evidence? Drawing on the theoretical framework of imaginaries from Science and Technology Studies (STS) and Critical Data Studies (CDS), this work lays the foundations for expanding CDS with Brazil, foregrounding the country as a vibrant site of epistemological and political contestation that resists post-factual truth regimes, far-right politics, and spaces of “strategic unknowns” (McGoey, 2012). Through the case of Abrario, a grassroots organization challenging exclusionary state and regulatory practices, the study reveals the frictions, negotiations, and power struggles inherent in contemporary data production. Abrario’s mobilization of community-generated data not only exposes the limits of "official" knowledge but also highlights the transformative potential of grassroots data to reshape dominant narratives about health, care, and citizenship. Centering perspectives from the Global South, this work moves beyond technical debates to explore the symbolic, political, and poetic dimensions of datafication. It conceptualizes grassroots data activism as part of epistemic sites, dynamic spaces of negotiation, translation, and imagination where alternative ways of knowing are produced and defended. The study uncovers tensions between bottom-up and top-down data regimes and highlights the forms of institutional skepticism that shape the rounds of legitimization required for grassroots evidence-making. By mobilizing mutiple data practices multiple formats Abrario’s activism actively challenges dominant data regimes that erase or marginalize the lived experiences of its community.